2021
DOI: 10.1093/plphys/kiab558
|View full text |Cite
|
Sign up to set email alerts
|

Auxin biosynthesis maintains embryo identity and growth during BABY BOOM-induced somatic embryogenesis

Abstract: Somatic embryogenesis is a type of plant cell totipotency where embryos develop from non-reproductive (vegetative) cells without fertilization. Somatic embryogenesis can be induced in vitro by auxins, and by ectopic expression of embryo-expressed transcription factors like the BABY BOOM (BBM) AINTEGUMENTA-LIKE APETALA2/ETHYLENE RESPONSE FACTOR (AP2/ERF) domain protein. These different pathways are thought to converge to promote auxin response and biosynthesis, but the specific roles of the endogenous auxin pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 85 publications
1
30
0
Order By: Relevance
“…The obvious differences in color, texture, morphology or histology between EC and NEC of different species have been reported in several studies ( Nagmani and Bonga, 1985 ; Maadon et al., 2016 ; Bravo et al., 2017 ; Gautier et al., 2019 ; Xue et al., 2022 ), but the most significant difference between EC and NEC is that EC cells have the potential to acquire totipotency, which can furtherly regenerate into a complete organism ( Condic, 2014 ; Horstman et al., 2017 ; Li et al., 2022b ). A number of plant TFs have been identified that can covert somatic cells into embryogenic, totipotent cells, in which BBM, WUS, and LEC1 have been highlighted in many studies ( Su et al., 2009 ; Horstman et al., 2017 ; Su et al., 2021 ; Wang et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obvious differences in color, texture, morphology or histology between EC and NEC of different species have been reported in several studies ( Nagmani and Bonga, 1985 ; Maadon et al., 2016 ; Bravo et al., 2017 ; Gautier et al., 2019 ; Xue et al., 2022 ), but the most significant difference between EC and NEC is that EC cells have the potential to acquire totipotency, which can furtherly regenerate into a complete organism ( Condic, 2014 ; Horstman et al., 2017 ; Li et al., 2022b ). A number of plant TFs have been identified that can covert somatic cells into embryogenic, totipotent cells, in which BBM, WUS, and LEC1 have been highlighted in many studies ( Su et al., 2009 ; Horstman et al., 2017 ; Su et al., 2021 ; Wang et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…SE is a complex process of embryo development involving cell dedifferentiation and reprogramming to regenerate whole plants, which is regulated by a network of hundreds of genes ( Mordhorst et al., 1997 ; Wang et al., 2020 ). Many studies focusing on plant SE were conducted in some short-lived angiosperms such as Cucumis sativus ( Xue et al., 2022 ), Gossypium hirsutum ( Guo et al., 2019 ; Kumar et al., 2021 ) , and Fragaria vesca ( Liu et al., 2022 ), and most in-depth knowledge of SE can be only obtained from Arabidopsis ( Horstman et al., 2017 ; Karami et al., 2021 ; Li et al., 2022b ; Paul et al., 2022 ). However, little is known from perennials including gymnosperm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FIS-PRC2 complex is responsible for the deposition of H3K27me3 marks in the female gametophyte and in the endosperm, and mutations in genes coding for its subunits leads to the failure of endosperm cellularization (40,55). Our previous chromatin immunoprecipitation sequencing data (6,56) showed that BBM directly targets the promoter of one of the FIS-PRC2 subunits, FERTILIZATION INDEPENDENT ENDOSPERM (FIE), a WD-40 protein that is homologous to Drosophila enhancer of zeste [E(z)] and that is expressed in both sporophytic and gametophytic tissues (57,58). BBM binds the FIE gene close to the protein translation start site and the bound region contains three BBM binding motifs (SI Appendix, Fig.…”
Section: Bbm and Plt2 Function Individually And Synergistically Tomentioning
confidence: 99%
“…BBM was first identified as a marker gene expressed in microsporederived Brassica napus embryos [32]. When ectopically expressed, the BBM gene induces embryo development from the cotyledon, leaf, and shoot apex in A. thaliana and from the hypocotyls of germinated seedlings in Brassica, without the application of exogenous hormones [32,36,37].…”
Section: Introductionmentioning
confidence: 99%